2013
DOI: 10.1021/ie300916d
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Azo Dyes from Water by Combined Techniques of Adsorption, Desorption, and Electrolysis Based on a Supramolecular Sorbent

Abstract: In this work, adsorption and desorption of azo dye-Congo red on a supramolecular sorbent (SiO2-CD) were studied. Static adsorption study showed that the adsorption of Congo red onto SiO2-CD obeyed Langmuir’s model. The sorbent may be easily regenerated by using β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD) as a desorption agent. The desorption efficiency of Congo red was strongly dependent on the concentration of the desorption agent and the temperature. The electrochemical degradation of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 50 publications
0
29
1
Order By: Relevance
“…These easy-to-prepare and reusable materials expect to be the promising for the treatment of aqueous solutions not only from benzene but also from its derivatives. For the last years, it was shown high adsorption efficiency of β-CD-containing adsorbents in the absorption of different aromatic compounds from water [14, 18, 2426, 29, 35, 36, 45, 46]. Nowadays, there is an increasing interest in the research and development of adsorbent with satisfying adsorption capacity, high mechanical strength, high reusability, and ready availability, especially the adsorbent based on natural products for their ready availability and excellent biocompatibility, which will not cause additional environmental pollution in their application [26, 45, 46].…”
Section: Resultsmentioning
confidence: 99%
“…These easy-to-prepare and reusable materials expect to be the promising for the treatment of aqueous solutions not only from benzene but also from its derivatives. For the last years, it was shown high adsorption efficiency of β-CD-containing adsorbents in the absorption of different aromatic compounds from water [14, 18, 2426, 29, 35, 36, 45, 46]. Nowadays, there is an increasing interest in the research and development of adsorbent with satisfying adsorption capacity, high mechanical strength, high reusability, and ready availability, especially the adsorbent based on natural products for their ready availability and excellent biocompatibility, which will not cause additional environmental pollution in their application [26, 45, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Polymer P.1 was found to be the best sorbent for MO (373 mg/g); composition 1 1 2 (497 mg/g) for AO5 and macrocycle 2 for CR (625 mg/g). In comparison with the last literature data, the sorption of MO and AO5 by P.1 and P.2 polymers has very high values (the sorption capacity for MO by Moringa peregrina ash is 35 mg/g (21), for AO5 by utilises canola stalks is 17 mg/g (22) and the sorption of CR has comparable values (by SiO 2 modified by b -cyclodextrin is 70 mg/g (23).…”
Section: Resultsmentioning
confidence: 59%
“…where q e (mg/g) is the amount of pollutant adsorbed at equilibrium, q max,e (mg/g) is the maximum adsorption capacity of adsorbent at equilibrium, c (mol/L) is the residual pollutant concentration at equilibrium, and K (L/mol) is the equilibrium constant. The well‐behaved linear relationship (see Figure S3 in Supporting Information) hasshown that the adsorption of MB onto β‐CD/g‐C 3 N 4 obey Langmuir's model (the correlation coefficient R 2 is close to 1) . According to the slope and the intercept of the straight line, q max,e and K both are respectively calculated to be 47.62 mg/g and 17355 L/mol, which are much larger than thoseof the pre‐exfoliated g‐C 3 N 4 (q max,e =15.87 mg/g and K=2801 L/mol).…”
Section: Resultsmentioning
confidence: 88%
“…According to the slope and the intercept of the straight line, q max,e and K both are respectively calculated to be 47.62 mg/g and 17355 L/mol, which are much larger than thoseof the pre‐exfoliated g‐C 3 N 4 (q max,e =15.87 mg/g and K=2801 L/mol). It's well‐known that the Langmuir equation was applicable to homogeneous adsorption, where theadsorption of each molecule onto the surface had equal adsorption activation energy, which suggested that the β‐CD/g‐C 3 N 4 composite possesses good dispersibility and has abundant functional groups and active sites for the removal of MB from wastewater system (more details are illustrated in Table S1‐2 and Figure S3).…”
Section: Resultsmentioning
confidence: 99%